A Bibliometrics Visualization Analysis of Sustainable Green Supply Chain Management in Small and Medium Enterprises - Rahmad Solling Hamid; Suriyanti Suriyanti; Imaduddin Imaduddin (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This bibliometric study entails an analysis of publications about green supply chain management (GSCM) within small and medium enterprises (SMEs). The research aims to scrutinize the research performance concerning GSCM in SMEs. This study identifies countries, leading journals, scholars, and research themes. This research adopts bibliometric methods to focus on publications between 2007 and 2024, sourced from the Scopus database and limited to English-language publications. The document type analyzed is articles, yielding 133 qualifying articles for analysis using Rstudio and VOSviewer. Results indicate rapid growth in studies on GSCM in SMEs since 2007. Influential countries in the realm of GSCM within SME contexts include China, Indonesia, India, Malaysia, and the United Kingdom. Furthermore, the Journal of Cleaner Production and author Le TT emerge as the most prolific scholarly output in this domain. Supply Chain Management, GSCM, and SMEs are frequently recurring keywords, totalling 407 keyword link strengths. Keyword analysis over time indicates a trend towards adopting newly pertinent terms such as human resources, technology, circular economy (CE), trade, and business. Thus, utilising GSCM signifies promising prospects for SMEs in the future. This study adopts bibliometric methods based on document-type articles from the Scopus database collected as of March 15, 2024. Publications based on document types such as conference papers, conference reviews, book chapters, and sources outside the Scopus database, such as WoS, are disregarded in this research. The study reveals that the sustainable implementation of GSCM in SMEs is an emerging requirement and complex to manage for SMEs, necessitating new concepts and appropriate strategies for implementation. This study objectively evaluates research progress in GSCM within SMEs, highlighting research achievements and gaps while discussing contributions to the scholarly community.